Congenital disorders of glycosylation in children - Histopathological and ultrastructural changes in the liver - Patryk Lipiński; Joanna Cielecka-Kuszyk; Elżbieta Czarnowska; Anna Bogdańska; Piotr Socha; Anna Tylki-Szymańska (Elsevier, 2021)
Background: Congenital disorders of glycosylation (CDG) result from defects in the synthesis of glycans and their attachment to proteins and lipids. Histologically, liver steatosis, fibrosis and cirrhosis have been reported in CDG.The aim of the study was to characterize the histopathological and ultrastructural liver changes in CDG patients hospitalized in our Institute, and to find the most characteristic features, as articles concerning the liver microscopic features in CDG are sparse. Methods: Out of 32 CDG patients diagnosed and followed-up in our Institute, the liver biopsy was performed in 4 of them, including 2 with MPI-CDG, 1 with SRD5A3-CDG, and 1 with PGM1-CDG, as a part of diagnostic process. In one patient, diagnosed post mortem with PMM2-CDG, the histopathological study comprised liver autopsy samples. Results: The most common histopathological liver finding was the presence of steatosis (4/5) of varying severity, the mixed macro- and microvesicular type as well as the foamy degeneration of hepatocytes. In two patients, liver steatosis was associated with fibrosis, stage 4 (cirrhosis) and 2 according to Batts and Ludwig classification, respectively. In two patients, besides steatosis, mild inflammatory infiltrates composed of lymphoid cells in portal tracts were observed. No correlation between the patient's age and histopathological features was observed. Conclusions: The histopathological changes in the liver of CDG patients are miscellaneous; thus, based on the microscopic examination only, we can not identify (even suspect) the exact CDG. The most common histopathologic finding in our cohort of CDG patients was the presence of liver steatosis (of various severity) and foamy degeneration of hepatocytes.